Chapter Habitat and flora monitoring in the Regional Nature Reserve of "Palude del Conte e Duna Costiera di Porto Cesareo" (Puglia, Italy) - Giannuzzi, Cosimo Gaspare (Proceedings e report, 2020)
This study describes the results of the monitoring activity on habitats and plant species in the Regional Nature Reserve of "Palude del Conte e Duna Costiera di Porto Cesareo" (Puglia, Italy) and in the adjoining special areas of conservation (SACs), in the period April-December 2018. The activity combined field vegetation surveys and interpretation of orthophotos on a GIS system. The study identifies the pressure and threat factors that negatively affect the conservation of habitats.